Quantative and Qualitative Analysis of Essential Oil Obtained From Turmeric Rhizomes - Malik, Nisha (My University, 2016)
Turmeric is common spice, widely used in Indian kitchen as food additive and preservatives. It is also used as effective medicines in Ayurveda. The essential oil is isolated from fresh turmeric rhizomes using modified steam distillation process. The obtain ed oil yield is compared with the oil obtained from conventional process. The oil yield from fresh rhizomes is obtained as~2.83 - 2.48%. The obtained yield is 13% more in rhizomes as compare to conventional processes. It is found that the loss of water solub le polar compound is less as compared to conventional process. The main constituents of turmeric essential oil are ar - turmerone, Curlone, Zingiberene, ar- curcumin, Dehydro curcumene and ~60% compound were not identified. Overall, the modified process is f easible to obtain the essential oil from the turmeric rhizomes with increase yield and reduced loss of polar compounds
Master of Science-Chemistry
Keywords: Turmeric; Modified Steam Distillation Process; Essential Oil; GC-MS